2015
DOI: 10.7324/japs.2015.501108
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal potential of the Seed and Leaf Foeniculum vulgare Mill essential Oil in liquid and vapor phase against phytopathogenic fungi

Abstract: Analysis of essential oils obtained from the seeds (SEO) and leaves (LEO) of Foeniculum vulgareMill cultivated in southeast of Morocco revealed that trans-anethole was the major constituent (54.67% of seed oil and 50.60% in leaf oil), followed by estragol (35.33% of seed oil and 30.15% in leaf oil). Other components present in leaf oil included fenchone, linalool and α-pinene, while seed oil contained fenchone, limonene and γ-terpinen. Besides, minor constituents like camphene, camphor, myrcene, pahllandrene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The components present in the volatile oil obtained from fennel are similar to those reported but the relative percentage of their as anethole and limonene differed (Chowdhury et al, 2009, Raal et al, 2012. While we showed that anethole and carvacrol were the main component of fennel oil, some papers reported that the main components of plant were methyl chavicol and anethole (Marotti et al, 1994) estragole and fenchone (Ozcan et al, 2006), anethole and estragole (Khalid et al, 2015). The chemical nature of volatile oils from Salvia species have mostly similar.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The components present in the volatile oil obtained from fennel are similar to those reported but the relative percentage of their as anethole and limonene differed (Chowdhury et al, 2009, Raal et al, 2012. While we showed that anethole and carvacrol were the main component of fennel oil, some papers reported that the main components of plant were methyl chavicol and anethole (Marotti et al, 1994) estragole and fenchone (Ozcan et al, 2006), anethole and estragole (Khalid et al, 2015). The chemical nature of volatile oils from Salvia species have mostly similar.…”
Section: Discussionsupporting
confidence: 80%
“…While we showed that anethole and carvacrol were the main component of fennel oil, some papers reported that the main components of plant were methyl chavicol and anethole (Marotti et al, 1994) estragole and fenchone (Ozcan et al, 2006), anethole and estragole (Khalid et al, 2015). The chemical nature of volatile oils from Salvia species have mostly similar.…”
Section: Discussionmentioning
confidence: 97%
“…Milenković et al (2022) reported that the main components in fennel leaf essential oil were anethole (51.4%), methyl chavicol (9.3%), p-Cymene (6.5%), α-phellandrene (5.9%) and β-phellandrene (4.9%). The fennel plants have characteristics with a dominant anethole content, and the yield in this study was 2.6 mL/Kg, as Khalid et al (2015) reported. In addition, the yield of essential oil from F. vulgare leaves from Tafilatet (Southeast of Morocco) was 2% (w/w) (Khammassi et al 2023).…”
Section: Discussionsupporting
confidence: 80%
“…Mycelial growth inhibition of Foa by plant extracts was assessed using the method described by Sellam et al [17] with slight modification. Five millimeters of mycelial discs from 7-day-old culture of Foa was transferred onto Petri dishes containing PDA medium supplemented with plant extracts as indicated above.…”
Section: Mycelial Growth Inhibitory Assaymentioning
confidence: 99%